Regional, structural, and demographic predictors of violent victimization: A cross-national, multilevel analysis of 112 countries. Issue 2 (May 2020) - Corcoran, Katie E; Stark, Rodney
Routine activities and lifestyles theories emphasize structural and demographic predictors that affect the opportunity to commit crime and the likelihood of being victimized. Past research tends to focus on either the individual- or country-level with few studies incorporating both. Additionally, past research primarily draws on the International Crime Victimization Survey, which results in small country samples that are biased toward developed nations. The current study uses data from a larger, more diverse sample that allow us to test whether findings from prior studies are generalizable. We are also able to theorize and test the effect of region on victimization. We find some differences between our findings and past research; we also identify that region is one of the strongest predictors of violent victimization.